Coastal residents, stingray style: Selecting the best intertidal creeks for seasonal living. (3rd April 2017) - Webb, Sarah; Carla Curran, Mary
ABSTRACT: Graphing and calculating percentages are integral skills in a STEM curriculum. Teaching students how to create graphs allows them to identify numerical trends and to express results in a clear and concise manner. In this activity, students will remain engaged in the lesson by moving around the room and then work together to generate their own data. Students will act like stingrays and determine the costs and benefits of selecting different habitats. The skills honed in the activity will enable students to compare actual stingray data with in-class data and to express the results graphically. This activity aligns with Ocean Literacy Principles, Common Core Standards, and National Science Education Standards. The Next Generation Science Standard of including the analysis and interpretation of data to provide evidence for the effects of resource availability on organisms in an ecosystem is also incorporated.